Manejo post-cosecha y comercialización del durazno (Prunus persica (L.) Batsch) - Ramírez Fajardo, Jesús; Puentes Montañez, Gloria A.; Delgado Zambrano, Antonio; Castro Silva, Alvaro (SENA, 2018)
Durazno-Prunus persica